Exploring the benefit of auditory spatial continuity - Best, Virginia (Acoustical Society of America, 2010)
Continuity of spatial location was recently shown to improve the ability to identify and recall a sequence of target digits presented in a mixture of confusable maskers [Best et al. (2008). Proc. Natl. Acad. Sci. U.S.A. 105, 13174–13178]. Three follow-up experiments were conducted to explore the basis of this improvement. The results suggest that the benefits of spatial continuity cannot be attributed to (a) the ability to plan where to direct attention in advance; (b) freedom from having to redirect attention across large distances; or (c) the challenge of filtering out signals that are confusable with the target.